The optimum size of Seoul's districts in South Korea. Issue 3 (5th July 2016) - Choi, Intae
Abstract : The optimum size of a city is marginal size when the city has inefficiencies in urban administration or the point that when a city loses attraction from citizens. This paper is examining optimal size of Seoul Autonomous Districts in South Korea. Because of the highly dense population in Seoul area, the government of South Korea is trying to solve this problem by implementing policies on developing non Seoul areas. However, it is important why Seoul in South Korea has abnormal dense population in comparison to other areas. Seoul is consisted of 25 autonomous districts and this paper found one autonomous district. Gangnam‐gu is a highly inefficient district comparing to other districts in Seoul. This finding can be a cause of dense population problem in Seoul. Copyright © 2016 John Wiley & Sons, Ltd.